Expression of matrix metalloproteases-2 and-9 in horse hoof laminae after intestinal obstruction, with or without Hydrocortisone treatment - Laskoski, Luciane Maria [UNESP]; Araujo Valadao, Carlos Augusto [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP]; Ferrucci, Danilo; Francisco Silva, Juliete Aparecida; Stach Machado, Dagmar Ruth; Sampaio Doria, Renata Gebara; Mendonca, Fabio de Sousa (Univ Federal Santa Maria, 2013)
Twenty horses were used in the experiment, for composed control group, (Cg) instrumented group, (Ig; without intestinal obstruction), treated group (Tg; submitted to intestinal obstruction and hydrocortisone treatment) and non-treated group (Ntg; submitted to intestinal obstruction without treatment). Immunohistochemistry and zymography techniques were used for researches on MMPs 2 and 9 in horse hoof laminae. There was an increase in the expression of MMP-2 in animals of Tg and Ntg. MMP-9 increased on animals from groups Ntg and Ig, however there was no rise of this MMP on the Tg when compared to the other groups in the immunohistochemistry analysis. Based on the results, it was observed that the intestinal injury caused by enterotomy and intestinal obstruction raise the quantities of MMPs in the hoof laminae.
Expressão de metaloproteinases 2 e 9 no tecido laminar do casco de equinos após obstrução intestinal e tratamento com hidrocortisona
Keywords: Horse; Immunohistochemistry; Laminitis; Metalloprotease; Zymography; Animalia; Equidae